Проблемы социально-экономической трансформации украинского общества - Бурега, В. (Социология: теория, методы, маркетинг, 1999)
The discussion of the social interaction of individuals during transformation of society is based on sociological data. Special attention is paid to such phenomena resulting from total destruction of value-normative system, as distortions inperception of the social space and time, sharp property stratification of thepopulation, changes of vital priorities of the representatives of all social groups, growth of criminality and so on. Proper effective administrative measures should be introduced to minimize and neutralize negative consequences of transformational processes in Ukraine.